KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH: PERSPEKTIF FAKTOR INTERNAL DAN EKSTERNAL - Faisol, Moh.; Rofik, Mohammad (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2019)
The quality of local government financial reports is a reflection of good localgovernment governance, as a tool to realize transparent and accountable financialaccountability. Internal and external factors can influence quality financial reports. Thequantitative method was chosen as a tool to solve this problem, by distributingquestionnaires to 33 SOPD in Sumenep Regency. Data analysis using multiple linearregressions. The results showed that the use of information technology, human resourcecompetence, regional financial supervision, internal control, implementation of SAP,good governance affected the quality of local government financial reports, both partiallyand simultaneously. 70% of the quality of local government financial reports can beinfluenced by variables X1, X2, X3, X4, X5, and X6.